2002
DOI: 10.1007/s11881-002-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic transfer in literacy development and implications for language learners

Abstract: One of the challenges for educators working in multilingual settings has been to identify the causes of reading difficulties of language learners (LLs). It is difficult to distinguish between reading problems stemming from low levels of linguistic proficiency versus more general reading~learning difficulties. There is now growing research evidence of cross-language transfer in different literacy processes. Literacy components that reflect language-independent, metacognitive/ metalinguistic processes show simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
160
0
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(186 citation statements)
references
References 46 publications
16
160
0
10
Order By: Relevance
“…These findings indicate that there is a relationship between phonological awareness skills in the two languages, corroborating the findings reported by . Also, these findings are in line with previous research in the Semitic language of Hebrew (Geva & Wang, 2001) as well as other alphabetic languages (Durgunoglu, 2002).…”
Section: Conceptual and Practical Issuessupporting
confidence: 92%
See 2 more Smart Citations
“…These findings indicate that there is a relationship between phonological awareness skills in the two languages, corroborating the findings reported by . Also, these findings are in line with previous research in the Semitic language of Hebrew (Geva & Wang, 2001) as well as other alphabetic languages (Durgunoglu, 2002).…”
Section: Conceptual and Practical Issuessupporting
confidence: 92%
“…For example, ample research exists that bilingual children in the US, whose main language is not English, are at risk for poor reading outcomes (National Center for Education Statistics, 2003). Some studies attribute this to weaknesses in phonological awareness (Durgunoglu, 2002;Geva, 2008) and morphological awareness skills that transfer from one language to another (Deacon & Wade-Woolley, 2005;Geva 2008). Other studies link poor outcomes to the children's diminished language experience.…”
Section: Bilingual Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…It was argued that proficiency in syntactic awareness demands of the reader metalinguistic insight allowing the subject to discern the internal grammatical structure of sentences (Durgunoğlu, 2002). Similar findings were found in another study, where syntactical awareness in Spanish as the L1 among students in the 4th grade, was highly correlated with syntactical awareness in English as the L2 (Durgunoğlu, Mir, & Ariño-Martí, 2002).…”
Section: Inter-linguistic Skills and The Difficulties In Processing Dsupporting
confidence: 72%
“…For example, studies Asian-Pacific Journal of Second and Foreign Language Education have revealed that bilingual children's linguistic skills, such as phonological awareness and morphological awareness in their home language, predict their acquisition of English literacy (e.g., Adams, 1990;Casalis & Louis-Alexandre, 2000;Durgunoğlu, 2002;Riches & Genesee, 2006;Snow et al, 1998;Wagner & Torgesen, 1987). In addition, a number of studies examining learning English as an L2 among children who speak an alphabetic L1 like Spanish, French or Italian have found that students' L1 proficiency level can facilitate their L2 learning (e.g., Cisero & Royer, 1995;Comeau et al, 1999;Durgunoglu et al, 1993;D' Angiulli et al, 2001).…”
Section: Introductionmentioning
confidence: 99%